A practical guide to diagnosing bovine mastitis: a review - Ramuada, Mpho; Tyasi, Thobela Louis; Gumede, Lungile; Chitura, Teedzai (Frontiers in Animal Science, 2024)
Mastitis is one of the major diseases affecting the viability of dairy farming due to direct and indirect losses associated with low milk yield and poor milk quality. This review aims to provide comprehensive literature on methods that are commonly employed for field and laboratory diagnosis of bovine mastitis. The search process was conducted with the use of the Google Scholar electronic database. The keywords were “bovine mastitis” and “diagnosis. Findings indicate the use of various tests for early detection of mastitis under field conditions and in the laboratory. Conventional methods include somatic cell count, microbiological milk culture, and the California mastitis test. Microbiome techniques and chromogenic plates were mentioned as methods that can yield better results as compared to simple bacterial culture methods. Polymerase chain reaction and matrix-assisted laser desorption/ionization-time of flight were mostly reported as reference tests for the diagnosis of bovine mastitis. The use of biosensors, machine learning and 16srRNA was reported to offer prospects for the diagnosis of bovine mastitis. Overall, results have shown that diagnostic techniques for mastitis play a crucial role in early pathogen detection, facilitating prompt treatment and reducing mastitis transmission. It can be concluded that bovine mastitis is prevalent in dairy cattle and places a significant economic burden on dairy farms worldwide. Therefore, accurate disease diagnosis is a critical step towards developing targeted intervention measures for udder health management.